2001
DOI: 10.1161/01.cir.103.15.2021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Postreperfusion Viability by Intravenous Myocardial Contrast Echocardiography

Abstract: Background-Although defects on intracoronary myocardial contrast echocardiography (MCE) indicate loss of viability after reperfusion, opacified segments may also exhibit persistent dyssynergy. Therefore, we related the intensity and texture of opacification produced by an intravenous contrast agent to histological findings to determine the characteristics of necrotic tissue by postreperfusion MCE. Methods and Results-MCE was performed by intravenous injection of 0.15 mL/kg QW7437 in 14 dogs who underwent 3-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…2,3,15,16 Methods for assessing the potentially viable myocardium include the use of postextrasystolic potentiation during left ventricular angiography, 17 the response of left ventricular contraction to an inotropic stimulus such as dobutamine, 2, 3, 15 evidence of uptake of thallium-201 in a dysfunctional region of myocardium, 3,6 positron emission tomography, 18 and intravenous myocardial contrast echocardiography (MCE). 19,20 Because of technical limitations, these methods cannot be applied in all hospitals. Compared with these methods, ultrasonic tissue characterization is simple; therefore, ultrasonic tissue characterization should be a new diagnostic modality for evaluating reversibly dysfunctional segments in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,15,16 Methods for assessing the potentially viable myocardium include the use of postextrasystolic potentiation during left ventricular angiography, 17 the response of left ventricular contraction to an inotropic stimulus such as dobutamine, 2, 3, 15 evidence of uptake of thallium-201 in a dysfunctional region of myocardium, 3,6 positron emission tomography, 18 and intravenous myocardial contrast echocardiography (MCE). 19,20 Because of technical limitations, these methods cannot be applied in all hospitals. Compared with these methods, ultrasonic tissue characterization is simple; therefore, ultrasonic tissue characterization should be a new diagnostic modality for evaluating reversibly dysfunctional segments in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The early reestablishment of epicardial coronary patency after thrombolysis or angioplasty is a determining factor for the restriction of the infarct size. Most of the recent data [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] have been focused on STEAMI and revealed that restoration of epicardial coronary artery patency is not equivalent to restoration of nutritive tissue flow [33]. Functional and structural microvascular disturbance-low or no reflow phenomenon-despite infarct artery patency, is an important pathophysiologic phenomenon in the setting of reperfused STEAMI.…”
Section: Detection Of Coronary Artery Diseasementioning
confidence: 99%
“…Echo textures was analyzed by using c ooccurrence matrices, which were constructed for each pixel in the area of interest comparing pairs of gray levels in surrounding pixels and evaluat ing related properties using second order statistics [1]. For each neighborhood the co-occurrence matrix is calculated and then the entropy of this matrix.…”
Section: Texture Analys Ismentioning
confidence: 99%
“…Considering the ability of MCE for assessing microvascular integrity, this technique may be useful for quantifying myocardial viability after sucessful reperfusion in acute myocardial infarction [1] and to estimate infarct size [2]. To quantitatively analyse the different patterns of myocardial opacification following coronary occlusion and reperfusion, in this study, we propose a method that is able to aggregate information from myocardial contrast images and tissue characterization analyzes to compose a my ocardial perfus ion and texture polar map of the left ventricle in an animal model of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%